CFD Investigation of Turbulence Behaviour in Grooved Divergent Rocket Nozzles using 2 the k-? Model (London Journal of Engineering Research, 2025)
The adiabatic gas expansion in the divergent rocket area generally results in the generation of thrust 19 required for propulsion by providing an environment where the gas molecules speed rapidly out the nozzle 20 exit after traversing the nozzle area. This study investigates the impact of wall grooving in the divergent 21 section of rocket nozzles on turbulence characteristics and flow performance using Computational Fluid 22 Dynamics (CFD). Employing the Finite Volume Method (FVM) and the k ? turbulence model in 23 ANSYS Fluent, the study compares a conventional nozzle and a grooved counterpart under identical 24 boundary conditions. Key parameters analyzed include Turbulent Kinetic Energy (TKE), Turbulent 25 Eddy Dissipation (TED), and velocity profiles. Results reveal that while the grooved nozzle slightly 26 reduces axial velocity, it significantly enhances turbulence dissipation and flow stability by suppressing 27 lateral velocity fluctuations. Enhanced TED and uniform TKE distribution suggest improved mixing 28 and thermal energy control, making grooved nozzles a promising modification for advanced propulsion 29 systems.
Keywords: Digital radiography; Multiscale analysis; Pixel-level fusion; Image detail enhancement; Nondestructive testing; turbulence; computational fluid dynamics.; Divergent Nozzle Grooving; Rocket nozzle; Flow field